Comparison of Outcomes between Open and Arthroscopic Rotator Cuff Repair - Serdar Menekse (Advances in Orthopedics)
Objective. The objective of this retrospective cohort study is to evaluate the long-term clinical and functional outcomes of two surgical techniques for rotator cuff repair, namely, open and arthroscopic methods. Methods. A total of 100 patients diagnosed with rotator cuff tears and treated at Seyhan State Hospital in the past five years were enrolled, considering the same inclusion criteria for both groups. The study groups consisted of 50 patients who underwent open rotator cuff repair and 50 patients who underwent arthroscopic rotator cuff repair. We used the SPSS programme to analyse the data, focusing on parameters such as postoperative recovery time, functional capacity scores, pain levels measured by the VAS scale, quality of life evaluated by the SF-36 scores, and complication rates. Results. Both methods resulted in similar recovery times and functional capacity scores, but patients treated with the open method reported slightly lower pain levels (average VAS score: 2.8) compared to those treated with the arthroscopic method (average VAS score: 3.1). The study also found slightly better quality of life scores in the arthroscopic group (average SF-36 score: 71.4) compared to the open surgery group (average SF-36 score: 68.7). The complications rates were lower in the arthroscopic group (2%) than in the open surgery group (4%), but these differences were not statistically significant. Conclusions. The study suggests that, while there are no significant differences in terms of clinical outcomes between the two surgical methods, short-term pain levels may be influenced by the more frequent application of acromioplasty in arthroscopic methods. Therefore, the choice of the surgical method should be made based on the unique characteristics, including the location and size, the patient’s overall health status, and the surgeon’s experience. These findings should be used as a guide and not as absolute results.